Levels of Fibrin Degradation Products at Admission With Acute Ischemic Stroke Correlate With the NIH Stroke Scale Score 1 h After Intravenous Thrombolysis - Zhu, Bin; Zhang, Limin; Du, Wanliang; Yang, Jie; Tian, Yue; Wu, Mingfen; Wu, Tingxi; Ling, Xi; Liu, Yilin; Zhao, Xingquan; Zhao, Zhigang (Frontiers in Neurology, 2021)
Background: Fibrin degradation products (FDPs) are fragments released by the plasmin-mediated degradation of fibrinogen or fibrin. Whether plasma levels of these fragments can predict the thrombolytic effect of recombinant tissue plasminogen activator (r-tPA) remains unknown. Methods:We performed a hospital-based study of patients with acute ischemic stroke (AIS) to explore the relationship between FDPs levels at admission and the NIH Stroke Scale (NIHSS) score 1 h after thrombolysis treatment. In this retrospective, single-center study, the data of all patients with AIS who received r-tPA treatment at Beijing Tiantan Hospital from January 2019 to October 2020 were collected and analyzed. Demographic and clinical data, including laboratory examinations, were also analyzed. Results: A total of 339 patients with AIS were included in this study. Of these, 151 showed favorable effects of r-tPA, and 188 showed unsatisfactory effects at 1 h after thrombolysis. Overall, we found an inverse relationship between the FDPs levels at admission and the NIHSS score. A significant difference was observed when using the interquartile range of the FDPs levels (1.31 µg/mL) as a cutoff value (P = 0.003, odds ratio [OR] = 1.95, 95% confidence interval [CI]: 1.26–3.01), even after adjusting for confounding factors (P = 0.003, OR = 2.23, 95% CI: 1.31–3.77). In addition, significant associations were observed in the tertile (T3) and quartile (Q3, Q4) FDPs levels when compared with T1 or Q1. A nomogram was also employed to create a model to predict an unsatisfactory effect of r-tPA. We found that FDPs levels, white blood cell count, age, D-dimer level, and body mass index can influence the thrombolytic effect of r-tPA. Conclusion: In conclusion, the present study demonstrated that the levels of FDPs at admission can be used as a prognostic factor to predict the curative effect of r-tPA.